Estrategias de marketing digital del fotógrafo Marcos Alberca en Instagram y Tik Tok, periodo Julio-Octubre 2023 - Cabrera Aldaz, Gustavo Paul (2025)
Global digitalization has transformed the world of marketing driving the creation of new strategies for the positioning of brands, companies or institutions, demonstrating its relevance in the rise of the digital era in the professional field. This research aims to analyze the various digital marketing strategies used by Marcos Alberca, a Spanish photographer recognized on platforms such as Tik Tok and Instagram. For this purpose, an exploratory study was used to describe the digital marketing strategies employed by the photographer in social networks; detailing the characteristics of his digital presence and the connection with his followers. At the methodological level, three observation sheets were carried out; the first one focused on the marketing strategies in his social networks; the second one analyzed the structure and characteristics of his audiovisual content; and the third one evidenced the interactivity with his followers. In addition, three interviews were conducted with marketing professionals to deepen the analysis of the case. The results allowed us to identify that Marcos Alberca's digital marketing strategies are effective, focusing on SEO, Content Marketing and Social Selling. On the other hand, its digital presence is characterized by a combination of audiovisual content, text and links in Instagram; while, in the social network Tik Tok highlights video and text, adapting to the specific characteristics of each platform. Likewise, the content that stands out to Marcos' followers is emotional and personal. Finally, a series of conclusions and suggestions are presented to improve the content and viralization of the brand, through the adaptation of other marketing strategies, the incorporation of AI and content variation